Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd007411.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for male subfertility

Abstract: The evidence suggests that antioxidant supplementation in subfertile males may improve the outcomes of live birth and pregnancy rate for subfertile couples undergoing ART cycles. Further head to head comparisons are necessary to identify the superiority of one antioxidant over another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 298 publications
(124 citation statements)
references
References 59 publications
5
112
0
3
Order By: Relevance
“…There are varied reports [116][117][118] on the efficiency of various antioxidant therapy in infertile men. Recent meta analysis [119,120] of these studies suggest that antioxidant therapy is beneficial and improves various indices of male fertility. However antioxidants should only be administered in cases with increased free radical levels as majority of enzymatic reactions in our body functions under redox conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are varied reports [116][117][118] on the efficiency of various antioxidant therapy in infertile men. Recent meta analysis [119,120] of these studies suggest that antioxidant therapy is beneficial and improves various indices of male fertility. However antioxidants should only be administered in cases with increased free radical levels as majority of enzymatic reactions in our body functions under redox conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review by Cochrane [38] was published to evaluate the effect of oral supplementation with different antioxidants for male partners of couples undergoing assisted reproduction techniques. Compared with the present study, Showell et al [38], which included only two trials, obtained comparable results and concluded that although the seminal parameters appeared to improve after supplementation with CoQ10, there was no change in the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…The damaging effects of oxidative stress on sperm are considered to be responsible for 30 % to 80 % of male subfertility cases [38]. It is well known that spermatozoa are susceptible to oxidative damage and reactive oxygen species (ROS), and numerous studies support the hypothesis that ROS are responsible for sperm dysfunction and male infertility [3,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations